The Effect of Marital Training Courses on Family Stability – An Applied Study in The City of Buraydah – - Alrasheed, Aisha Abdallah (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the effect of rehabilitation training courses for marriage and its relationship to achieve family stability from social side, economic side, and legal jurisprudence side. Also, it aimed to identify the effect of some independent variables which contain the number of sons, the possibility to get a job, and the level of income for the family. To achieve this, the study is based on the comparative descriptive approach, and the questionnaire method was used to collect data. The study was applied, in Ossrah Association, Buraydah, to a random sample of (644) wives, married women of pre-marital rehabilitation training courses on family stability, and married women who did not have pre-training rehabilitation training courses on family stability. The data were processed by using statistical tests (frequency, percentage, difference test, T-T test, and the predicative analytical factor). In light of the assumptions of the explained theory, the study revealed several results: The assumptions of the social behavioral theory were appropriate to explain the effect of rehabilitation training courses for marriage on family stability. Therefore, the study is based on understanding the nature of family stability and its relationship with rehabilitation training courses for marriage. The contribution of the rehabilitation courses for marriage demonstrates the social family stability, and this was evident in concern with the value of the arithmetic average in the majority of the sub-indices in favor of the wives who got the rehabilitation training courses for marriage. On the other hand, it was also evident that the contribution of rehabilitation training courses for marriage did not contribute to economic family stability, as well as, this was evident in concern with the value of the average arithmetic in the majority of sub-indices in favor of wives who did not receive rehabilitation training courses for marriage.